Development of the Korean framework for senior-friendly hospitals: a Delphi study - Yoon-Sook Kim; Seol-Heui Han; Jeong-Hae Hwang; Jae-Min Park; Jongmin Lee; Jaekyung Choi; Yeonsil Moon; Hee Joung Kim; Grace Jung Eun Shin; Ji-Sun Lee; Ye Ji Choi; Kyeong Eun Uhm; et al. (BMC, 2017)
Abstract Background Aging is an inevitable part of life. One can maintain well-being and wellness even after discharge and/or transition if his or her functional decline is minimized, sudden decline is prevented, and functioning is promoted during hospitalization. Caring appropriately for elderly patients requires the systematic application of Senior-Friendly Hospital principles to all operating systems, including medical centres' organization and environment, as well as patient treatment processes. The Senior-Friendly Hospital framework is valid and important for patient safety and quality improvement. This study aimed to make recommendations regarding the development of the Korean Framework for Senior-Friendly Hospitals for older patients' care management, patient safety interventions, and health promotion, via a Delphi survey. Methods Two rounds of Delphi surveying were conducted with 15 participants who had at least 3 years' experience in accreditation surveying and medical accreditation standards, survey methods, and accreditation investigator education. In each round, we calculated statistics describing each standard's validity and feasibility. Results The Korean Framework for Senior-Friendly Hospitals included 4 Chapters, 11 categories, and 67 standards through consensus of the Senior-Friendly Hospitals task force and experts' peer review. After the two rounds of Delphi surveying, validity evaluation led to no changes in standards of the Senior-Friendly Hospitals; however, the number of standards showing adequate validity decreased from 67 to 58. Regarding feasibility, no changes were necessary in the standards; however, the number of categories showing adequate feasibility decreased from 11 to 8 and from 67 to 30, respectively. The excluded categories were 3.2, 4.2, and 4.3 (service, transportation, and signage and identification). The highest feasibility values were given to standards 2.1.1, 4.1.4, and 4.1.6. The highest feasibility score was given to standard 2.4.2. Conclusions The Korean Framework for Senior-Friendly Hospitals needs to include 4 Chapters, 8 categories, and 30 standards. The Accreditation Program for Healthcare Organizations should include Senior-Friendly Hospitals -relevant standards considering Korea's medical environment.